Allein mit Lebensmittelkarten ist es nicht auszuhalten ... Autoren- und Verlegerbriefe 1945 - 1949 - Faber, Elmar 1934-2017 Hrsg (Aufbau-Taschenbücher, 1991)
enth. u. a. Johannes R. Becher, Bertolt Brecht, Willi Bredel, Hans Fallada, Gerhart Hauptmann, Lion Feuchtwanger, Wieland Herzfelde, Victor Klemperer, Heinrich Mann, Anna Seghers, Ehm Welk, Friedrich Wolf, ...